ANALISIS KESUKSESAN WAREHOUSE DIGITALIZATION (WADIG) MENGGUNAKAN MODEL DELONE DAN MCLEAN (STUDI KASUS : ASTRA MOTOR) - Paujiah, Syifah; Agushinta R., Dewi; Nursanta, Edy (Jurnal Nasional Teknologi Komputer, 2022)
The performance of Supply Chain Management and information strategies cannot be ignored for expanding the business. Sharing information in a technology-based supply chain or commonly called Digitalization Supply Chain (DSC) is very important. Astra Motor has developed a DSC application called WArehouse DIGitalization (WADIG) since 2016. The application has been implemented in most Honda Sales Operation (HSO) branches in March 2018. After an information system penetrates the implementation phase in the life cycle of information system development, a post-implementation review is required. The effectiveness of WADIG (how far the system can reach its goals) and the factors that influenced the successful implementation of the application were examined and analyzed. This research used the success model of The Updated DeLone &McLean information system. Before data processing using SmartPLS, validity, reliability, and linearity tests of each indicator include service quality, information quality, system quality, user satisfaction, and individual impact conducted. The statistical results showed that the WADIG application is successful in providing benefits for its users